2020
DOI: 10.1002/2050-7038.12316
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conductor selection and capacitor placement in radial distribution system using nonlinear AC load flow equations and dynamic load model

Abstract: Summary This paper presents a mixed integer nonlinear programming (MINLP) model to solve the conductor gradation optimization problem of radial distribution systems. The conductor size selection and capacitor allocation problem are solved using exact AC load flow equations. The dynamic load characteristics have been considered in this model. The main objective is to realize both the thermal limit constraints and the bus voltage limit constraints. This is done while minimizing the capital cost of the conductors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The computation module assesses the technical and economic performance of the CSS process. Key technical considerations in passive CSS design include voltage drop, conductor loading, and power losses on the network [36]. On the other hand, active networks have a wider range of challenges, that require additional assessments including the analysis of voltage rise conditions, and network HC [38], [39].…”
Section: Scoping the Css Problemmentioning
confidence: 99%
“…The computation module assesses the technical and economic performance of the CSS process. Key technical considerations in passive CSS design include voltage drop, conductor loading, and power losses on the network [36]. On the other hand, active networks have a wider range of challenges, that require additional assessments including the analysis of voltage rise conditions, and network HC [38], [39].…”
Section: Scoping the Css Problemmentioning
confidence: 99%
“…where R ij is the line resistance between buses i and j, P j denotes the total effective active power supplied beyond the node j, Q j denotes the total effective reactive power supplied beyond the node j and |V j | is the voltage magnitude at bus j. The value of LSF for bus j (end bus) can be obtained by Equation (8).…”
Section: Lsfmentioning
confidence: 99%
“…Although CPP has been solved by using just FPA, final result may be a local optimal. In Reference 8, CPP and conductor size selection have been solved by using mixed integer linear programming (MILP) model considering AC load flow equations. Objectives of this work are minimization of capacitor and conductor costs as well as energy loss cost.…”
Section: Introductionmentioning
confidence: 99%
“…A sample of studies investigating the formulation of optimal CSS is reported in [1,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Analysis of this literature was carried out to establish the number of studies that considered DERs in the CSS formulation.…”
mentioning
confidence: 99%
“…Additionally, these studies did not consider modeling DERs, which implies that they are not suitable in selecting and sizing conductors in active systems. Furthermore, these methods were largely formulated with a cost minimization objective and did not envision enhancing DER penetration on the network as a key objective [17,[19][20][21][22][23][25][26][27][28][29][30][32][33][34]36].…”
mentioning
confidence: 99%